뇌사자 장기이식에 대한 수술실 간호사의 태도와 삶의 의미가 간호윤리 가치에 미치는 영향 - 서형은(Seo, Hyung-Eun); 김미영(Kim, Miyoung) (Sŏngin Kanho Hakhoe chi, 2016)
Purpose: The purpose of study was to describe operation room nurses' ethical values in relationship to the attitude and meaning of life toward organ transplantation in brain death. Methods: This study used a descriptive correlational survey design. Participants were 174 nurses who had attended to organ transplantation surgery in brain death more than once. Data were collected from September 1 to 11, 2015 and were analyzed using independent t-test, ANOVA, $Scheff{\acute{e}}$ test, Pearson's correlation coefficients, and hierarchical multiple regression with SPSS 22.0. Results: Educational level, attitude on organ transplantation in brain death, and meaning of life were significant variables predicting the level of nursing ethical value, accounting for 82.6% of the variability. Conclusion: Continued education and self-development programs should be encouraged for operating room nurses to establish professional nursing ethics as well as positive meaning of life and attitude toward the organ transplantation in brain death.